Odpowiedzi

2010-01-19T18:01:20+01:00
A)6x-3+4x=10x-3
b)14x+10-6x+12=8x+22
c)-16x+2x-5x²-15x=-29x-5x²
d)8-10x-(12x+18)=8-10x-12x+18=-22x+26
2010-01-19T18:02:15+01:00
A) 3(2x-1)+4(1-x)
b) 2(7x+5)-6(x-2)
c) -2x(8-x)-5(x²+3x)
d) 5(3-2x)-(4x+6)•3

a) 6x - 3 + 4 - 4x = 2x + 1
b) 14x + 10 - 6x + 12 = 8x + 22
c) -16x + 2x² - 5x² - 15x = -31x - 3x²
d) 15 - 10x + 12x + 18 = 2x + 33
2010-01-19T18:02:41+01:00
A) 3(2x-1)+4(1-x)
6x-3+4-4x
2x+1

b) 2(7x+5)-6(x-2)
14x+10-6x+12
8x+22

c) -2x(8-x)-5(x²+3x)
-16x+2x²-5x²-15x
-31x-3x²

d) 5(3-2x)-(4x+6)•3
15-10x+12x+18
33+2x


Pozdro;)